2019
DOI: 10.1377/hlthaff.2018.05049
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act In The Heart Of The Opioid Crisis: Evidence From West Virginia

Abstract: West Virginia is the epicenter of a national opioid crisis. We examine trends in treatment for opioid use disorder (OUD) among individuals enrolled in the West Virginia Medicaid expansion program under the Affordable Care Act using 2014-2016 claims data. Expanding Medicaid could provide services to populations that may previously have had limited access to OUD treatment. We thus sought to understand trends over time in OUD diagnosis and treatment, especially with medications. About 5.5% of all enrollees were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…8 In West Virginia, the state with the highest rate of deaths from opioid-involved overdose as of 2018, 9 buprenorphine prescriptions for patients with opioid use disorder increased by an estimated 42% between 2014, when Medicaid was first expanded in the state, and 2016. 10 Treatments with buprenorphine and methadone were associated with 38% and 59% decreases in opioid-related mortality, respectively, according to one study in Massachusetts; all forms of MAT should be made accessible. 11 US President Donald Trump has repeatedly called for the repeal of the ACA, which would roll back Medicaid expansion.…”
Section: The Opioid Crisis and The 2020 Us Election: Crossroads For A National Epidemicmentioning
confidence: 99%
“…8 In West Virginia, the state with the highest rate of deaths from opioid-involved overdose as of 2018, 9 buprenorphine prescriptions for patients with opioid use disorder increased by an estimated 42% between 2014, when Medicaid was first expanded in the state, and 2016. 10 Treatments with buprenorphine and methadone were associated with 38% and 59% decreases in opioid-related mortality, respectively, according to one study in Massachusetts; all forms of MAT should be made accessible. 11 US President Donald Trump has repeatedly called for the repeal of the ACA, which would roll back Medicaid expansion.…”
Section: The Opioid Crisis and The 2020 Us Election: Crossroads For A National Epidemicmentioning
confidence: 99%
“…Federal support for the Medicaid expansion must continue and the 14 states that have not expanded Medicaid should be incentivized to do so [ 19 ]. Recent studies have shown that expansion of health care services, mostly via Medicaid expansion, increased utilization of MOUD [ 3 , 41 , 42 ]. Expanding access to health coverage is necessary to prevent and treat the infection, underlying SUD, and improve overall mortality and quality of life as evidenced by studies finding an association between enrollment in an Affordable Care Act Qualified Health Plan and improved outcomes for people with HIV [ 43 ].…”
Section: Policy Recommendations For Driving Rapid Changes To Reduce Imentioning
confidence: 99%
“…Data indicates that West Virginia consistently ranks among states with the highest percentage of people experiencing mental health problems and encompass depression, anxiety, schizophrenia, and bipolar disorder (14). Genetic and genomic testing are performed for different purposes, such as identifying carriers, predicting a disease onset in presymptomatic individuals, or con rming a diagnosis, and such information may have notable psychological effects, such as generating anxiety and depression (15).…”
Section: Introductionmentioning
confidence: 99%